Evaluation of the efficacy of a 5% calcium sodium phosphosilicate (Novamin®) containing dentifrice for the relief of dentinal hypersensitivity: A clinical study - K S Rajesh; Shashikanth Hedge; M S Arun Kumar; Deepa Gajendra Shetty (Wolters Kluwer Medknow Publications, 2012)
Context: Dentinal hypersensitivity (DH) is a commonly encountered problem. Several products are used in management of DH with varying results. Need is felt in dentistry for a material that chemically reacts, physically occludes and adheres intimately to dentinal tubules to reduce the possibility of its recurrence. One such material is calcium sodium phosphosilicate-Novamin ® . Aim: To evaluate an efficacy of a 5% calcium sodium phosphosilicate (Novamin ® SHY NM TM ) containing dentifrice compared to placebo for the relief of DH. Settings and Design: Outpatients visiting Dept of Periodontics, Yenepoya Dental College with DH were deemed eligible for this case-control clinical trial after an informed consent. Materials and Methods: 30 patients having at least 2 sensitive teeth with a VAS (Visual Analogue Scale) of >3 cm after air blast stimulation, qualified to participate in the study. Test (SHY NM TM toothpaste containing 5% calcium sodium phosphosilicate) and control (Pepsodent toothpaste without a desensitizing agent) groups, each containing 15 participants, were subjected to cold water and air blast stimulation for an assessment of DH at baseline, 6 th and 8 th week using VAS. Statistical analysis used: Unpaired t-test and repeated measures ANOVA. Results: 5% Novamin ® containing dentifrice significantly reduced DH within 6 th and 8 th week of usage when compared to a placebo dentifrice. Conclusions: A Novamin ® containing dentifrice significantly reduced DH when compared to a placebo dentifrice.